2016
DOI: 10.1016/j.conbuildmat.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pristine and retrofitted hybrid steel/fibre reinforced polymer composite shear walls

Abstract: 28In this study new types of advanced hybrid shear wall systems using steel/fibre reinforced 29 polymer (FRP) composites are being developed for deployment in the construction of 30 buildings. The hybrid steel/FRP shear walls made from laminates of steel with either carbon 31 FRP (CFRP) or glass FRP (GFRP) materials. In total six medium-scaled shear wall 32 specimens were manufactured. In the first phase of the study three pristine specimens: steel 33 shear wall (SSW-P), hybrid steel /CFRP shear wall (HSCSW-P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
11
2
Order By: Relevance
“…HSWs are innovative structural lateral load resisting system and have significant advantages in comparison with steel shear wall systems. These include increased in-plane stiffness and load carrying capacity of the system and more uniform distribution of the tension field resulting in reduction of out-of-plane deformations in the infill plate [14,7].…”
Section: Hybrid Steel/frp Shear Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…HSWs are innovative structural lateral load resisting system and have significant advantages in comparison with steel shear wall systems. These include increased in-plane stiffness and load carrying capacity of the system and more uniform distribution of the tension field resulting in reduction of out-of-plane deformations in the infill plate [14,7].…”
Section: Hybrid Steel/frp Shear Wallsmentioning
confidence: 99%
“…Structural elements with carbon FRP (CFRP) and glass FRP (GFRP) are becoming popular in thin walled structures, sandwich panels and shear walls due to the combination of benefits from different materials. Initial research about FRP repair and straightening of damaged SSW and hybrid SW indicates opportunities for fast and effective recovery of the capacity of the damaged shear walls of this type [7].…”
Section: Introductionmentioning
confidence: 99%
“…As proposed by Teng et al (2007, 2012), the FRP composites can effectively enhance the seismic resistance of steel structures. Attempts on the steel shear plates were made by Petkune et al (2016, 2018), and the results indicated that the carbon fiber reinforced polymer (CFRP) could significantly improve the deformability and energy absorption of the plates with less loss in the stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The response of steel based fiber-metal laminates under various loading conditions is very interesting since steel is a classical construction material and their applications can be numerous. Recently, scientific articles concerning fiber-metal laminates with steel metal layers have been published [1][2][3][4][5][6][7][8][9]. In these articles, various applications are considered: thick walled tubes subjected to axisymmetric internal pressure [9], shear walls for the construction of buildings [6], panels for underwater applications [5] and industrial applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientific articles concerning fiber-metal laminates with steel metal layers have been published [1][2][3][4][5][6][7][8][9]. In these articles, various applications are considered: thick walled tubes subjected to axisymmetric internal pressure [9], shear walls for the construction of buildings [6], panels for underwater applications [5] and industrial applications [4]. The mechanical evaluation of steel based fiber-metal laminates includes their impact response, fatigue characteristics, creep behavior, hygrothermal conditioning, response to earthquake loading [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%